Tracing the Evolution of Sex Hormones and Receptor‐Mediated Immune Microenvironmental Differences in Prostate and Bladder Cancers: From Embryonic Development to Disease - Dengxiong Li; Zhipeng Wang; Qingxin Yu; Jie Wang; Ruicheng Wu; Zhouting Tuo; Koo Han Yoo; Dilinaer Wusiman; Luxia Ye; Yiqing Guo; Yubo Yang; Fanglin Shao; et al. (Advanced Science)
Abstract The bladder and prostate originate from the urogenital sinus. However, bladder cancer (BC) is usually classified as an immune “hot” tumor, whereas prostate cancer (PCa) is deemed as an immune “cold” tumor according to the tumor microenvironment (TME) and clinical outcomes. To investigate the immune differences between BC and PCa, studies are compared focusing on immune regulation mediated by sex hormones and receptors to identify key genes and pathways responsible for the immune differences. From a developmental perspective, it is shown that PCa and BC activate genes and pathways similar to those in the developmental stage. During prostate development, the differential expression and function of the androgen receptor (AR) across cell types may contribute to its dual role in promoting and inhibiting immunity in different cells. Androgen deprivation therapy affects AR function in different cells within the TME, influencing immune cell infiltration and antitumor function. Additionally, estrogenα and estrogenβ exert contrasting effects in PCa and BC, which may hold the potential for modifying the “cold” and “hot” tumor phenotypes. Future research should target key genes and pathways involved in bladder development to clarify the immune regulatory similarities and differences between BC and PCa.